A macromolecular α-glucan from fruiting bodies of Volvariella volvacea activating RAW264. 7 macrophages through MAPKs pathway. (15th February 2020) - Cui, FengJie; Jiang, LiHua; Qian, LiShun; Sun, WenJing; Tao, TingLei; Zan, XinYi; Yang, Yan; Wu, Di; Zhao, Xiu
Highlights: A novel polysaccharide VGPⅠ-a was purified from V. volvacea fruiting bodies. VGPⅠ-a was a macromolecular α-d -glucan. VGPⅠ-a formed a small screw-rod structure and a dispersed appearance. VGPⅠ-a significantly stimulated the release and mRNA expression of NO, TNF-α, IL-6 and IL-1β. VGPⅠ-a exerted immunoenhancing effects via MAPK signaling pathway. Abstract: A novel macromolecular polysaccharide VGPⅠ-a was purified from Volvariella volvacea fruiting bodies with ultrasound-assisted extraction, ion exchange and gel chromatography. VGPⅠ-a was proved as a α- glucan with Mw of 1435.6 kDa and contained a 1, 4-linked d -Glc p backbone with the substitution at C-6 with 1-linked d -Glc p residue. Congo-red test, AFM and SEM analysis showed VGPⅠ-a had a triple-helical conformation and the interacted chains to form a small screw-rod and dispersed appearance. VGPⅠ-a had no cytotoxic effect on macrophage RAW264.7 cells in vitro and significantly enhanced the production and mRNA expression of NO, TNF-α, IL-6 and IL-1β in a dose-dependent manner. Further analyses demonstrated that VGPⅠ-a activated the MAPK signaling pathway by improving the phosphorylated levels of p38, JNK and ERK in RAW264.7 cells to promote the expression and secretion of above cytokines. These findings would provide a better understanding of V. volvacea glucan and its potential immunomodulating mechanisms.